The Cnoc Dubh quarry and future comparative work (Scottish Historical and Archaeological Internet Reports, 2004)
The author had intended to compare the site with others in Scotland, however, it would be difficult to separate the results of the recent impact of geologists and amateur knappers. Cnoc Dubh therefore has enhanced importance and it is hoped that the site will in some way be protected.